Education of healthy toddlers through holistic parenting and complementary care - Tri Sunarsih; Endah Puji Astuti; Sujono Riyadi; Elvika Fit Ari Shanti (Community Empowerment, 2023)
Stunted growth in the early years of life can have dire consequences for a child's health. This community service aims to increase parents' and early childhood educators' understanding of early childhood parenting, characteristics that exist in child development, early detection of child development and complementary care that supports child growth and development. The implementation of this community service program uses the parenting education method and examines the growth of toddlers by applying several techniques, namely lectures, display studies, discussions, and examinations. The evaluation results showed that knowledge related to holistic parenting before education was 58.33% for the good category and increased to 100% after education. This shows an increase in participants' understanding of holistic parenting and complementary care.